DAMPAK PENERAPAN PUNGUTAN EKSPOR CRUDE PALM OIL TERHADAP KINERJA AGRIBISNIS KELAPA SAWIT DAN PENDAPATAN PETANI INDONESIA - ., Maswadi (Jurnal Social Economic of Agriculture, 2012)
Crude Palm Oil (CPO) is a strategic commodity in the economy ofIndonesia. CPO industry also plays an important role in the internationalmarket. The rate of growth of production of CPO is the highest among thecategories of oil consumed. Even a CPO has predicted will pass trade oilfor soybeans at most in the world market be trading.The current Government had new instruments in international tradeactivities, i.e. the export levy of dilegalisasi on September 10, 2005 withthe publication of legislation No. 33 of 2005. Broadly speakingstakeholders agribusiness palm national associate substance of the purposeand size of the export levy rate as well as benchmark price export withbenefit dimension, justice and legal certainty. After looking closely atlegislation of the export levy in the perspective of the development of oilpalm industry, there are 2 national article that needs to be understood indepth. The second chapter is chapter 2, about the purpose and article 3paragraph 5 and 6, of the size of export the levy rate and export benchmarkprices. Both articles still contain questions like: "whether its value hasbeen considering concrete benefits for all palm oil stakeholders national,meet the sense of justice and legal certainty in their implementation?".The review of this paper aims to discuss about the purpose of theapplication of the export levy and export benchmark prices taking intoaccount its benefits for all stakeholders to the national burden of palm oil,which must be borne by the stakeholders and legal certainty, and theirimpact on the performance of the agribusiness palm and farmer income inIndonesia.Keywords : Crude Palm Oil, Export Levy, Indonesia